2015
DOI: 10.1111/jvh.12447
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus coinfection independently increases the risk of cardiovascular disease in HIV‐positive patients

Abstract: Patients infected with HIV are at increased risk for cardiovascular disease despite successful antiretroviral therapy. Likewise, chronic hepatitis C virus (HCV) infection is associated with extrahepatic complications, including cardiovascular disease. However the risk of cardiovascular disease has not been formally examined in HIV/HCV-coinfected patients. A retrospective study was carried out to assess the influence of HCV coinfection on the risk of cardiovascular events in a large cohort of HIV-infected patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 35 publications
1
50
1
2
Order By: Relevance
“…15,16,37 The relative impact of the observed increase in LDL concentration associated with HCV clearance, shown here and in other studies, with the decrease observed in other biomarkers of cardiovascular disease observed with HCV clearance on subsequent risk for cardiovascular events requires prospective evaluation. 38 We also demonstrate that an LDL increase occurs with slower kinetics than the decline in HCV viral load in serum during treatment (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16,37 The relative impact of the observed increase in LDL concentration associated with HCV clearance, shown here and in other studies, with the decrease observed in other biomarkers of cardiovascular disease observed with HCV clearance on subsequent risk for cardiovascular events requires prospective evaluation. 38 We also demonstrate that an LDL increase occurs with slower kinetics than the decline in HCV viral load in serum during treatment (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Whether HCV clearance and changes in LDL will impact the higher rates of cardiovascular events associated with chronic HCV infection, and observed in some studies of HIV/HCV-coinfected relative to HIVmonoinfected subjects, will require prospective study in large patient cohorts. 16,37 In HIV-infected subjects receiving IFNfree treatment for HCV, lipids should be monitored posttreatment for cardiovascular risk assessment and determining indications for lipid-modulating therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that inhibition of this co-receptor produces an anti-inflammatory and anti-atherogenic effect (1)(2)(3)(4)(5). A body of evidence has documented that in patients with HIV, atherosclerosis is accelerated and chronic inflammatory processes are activated (6)(7)(8)(9); furthermore, certain evidence indicates that hepatitis C (HCV) co-infection can augment the risk of cardiovascular events (10,11). Moreover, hepatic stellate cells, that play an important role in the pathogenesis of liver fibrosis, express both HIV CCR5 and C-X-C chemokine receptor type 4 (CXCR4) co-receptors.…”
mentioning
confidence: 99%
“…While this general trend has been well documented, estimating and understanding the exact mechanisms and proportional contributions of these varied, potential causes of mortality among HCV-infected individuals remains more elusive [23]. HCV infection has been linked to a variety of nonhepatic morbidities, including Hodgkin’s lymphoma [24], gestational diabetes [25], cardiovascular disease [19, 26], non-liver cancers [27], renal disease, and stroke [28]. Many studies of non-hepatic disease burden among people with HCV infection also tend to focus on particular groups, such as HIV and HCV co-infected patients [29, 30], diabetics [31], and blood donors [32].…”
Section: Introductionmentioning
confidence: 99%